Low generational cystamine core PAMAM derivatives modified with nuclear localization signal derived from lactoferrin as a gene carrier - Lee, Jeil; Kwon, Yong-Eun; Guim, Hwanuk; Jeong, Kyung Jae (The Korean journal of chemical engineering, 2023)
Polyamidoamine (PAMAM) dendrimer has received much attention as an alternative to polyethylenimine (PEI) for gene delivery due to the relatively low cytotoxicity. In general, low generational PAMAM dendrimers have better biocompatibility than high generational dendrimers but suffer reduced transfection efficiency. Transfection efficiency can be improved by the modification of the polymer with nuclear localization signal (NLS) peptides. In this study, we modified low generational cystamine core PAMAM dendrimers (cPAMAM, generation 0, 1 and 2) with a lactoferrin-derived nuclear localization signal (NLS) peptide and evaluated transfection efficiency and cytotoxicity as a function of the number of conjugated NLS peptides using NIH 3T3, MCF-7 and human dermal fibroblasts (HDFs). The transfection efficiency of NLS-modified cPAMAM G2 was the highest among the cPAMAM derivatives and similar or higher than PEI 25 kDa. The cytotoxicity of cPAMAM derivatives was generation-dependent and significantly lower than PEI 25 kDa. Our study indicates that cPAMAM G2 conjugated with NLS is a promising candidate for gene delivery applications.